2021
DOI: 10.1080/14397595.2020.1869370
|View full text |Cite
|
Sign up to set email alerts
|

Association of methotrexate use and lymphoproliferative disorder in patients with rheumatoid arthritis: Results from a Japanese multi-institutional retrospective study

Abstract: Objectives To investigate the risk factors and clinical characteristics of lymphoproliferative disorder (LPD) in Japanese patients with rheumatoid arthritis (RA). Methods We enrolled patients with RA aged ≥20 years who visited the participating hospitals between April 2011 and July 2011. We investigated the risk factors for LPD using a Cox proportional hazard model and described pathological features and vital prognosis of LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
2
28
1
Order By: Relevance
“…This data suggested that patients with RA have an overall increased risk of developing cancer by 10% over the general population. Much evidence suggests that patients with RA have a significantly increased risk of lymphoma and lung cancer [ 14 20 ]. Lymphoma may be associated with MTX and bDMARDs in RA patients [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data suggested that patients with RA have an overall increased risk of developing cancer by 10% over the general population. Much evidence suggests that patients with RA have a significantly increased risk of lymphoma and lung cancer [ 14 20 ]. Lymphoma may be associated with MTX and bDMARDs in RA patients [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence suggests that patients with RA have a significantly increased risk of lymphoma and lung cancer [ 14 20 ]. Lymphoma may be associated with MTX and bDMARDs in RA patients [ 14 16 ]. And it was found that the higher the disease activity, the higher the relative risk [ 18 ], which is similar to the conclusion of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, various drugs to improve immune disorders and fibrosis have been used, 5 and recently, SHARE initiative has provided a recommendation based on expert opinion 6 that recommends corticosteroids, methotrexate (MTX), mycophenolate (MMF), or cyclophosphamide (CY), while hematopoietic stem-cell transplantation (HSCT) has been also recommended. However, from the experience of treating Japanese patients with rheumatoid arthritis, adverse reactions by MTX such as interstitial pneumonitis, liver injury, and lymphoproliferative disease tend to be more frequent in Japanese patients compared with other races 7 , 8 and coexisting ILD makes it difficult to use this agent. On the contrary, clinical trials have shown the effectiveness of CY in SSc, but these focused on patients older than 17 years of age, while some are retrospective studies or without control population.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate use was linked with lymphoma as it was thought to adversely affect recognition of EBV-infected B lymphocytes; however, this evidence focused on patients with RA (where the risk of lymphoma is increased) often compared against the general population 23. A further retrospective study did, however, identify methotrexate as a risk factor for lymphoproliferative disorders versus non-use 24. Ultimately, there is little evidence to support that methotrexate alone is associated with malignancy in the context of IBD, although this may relate to small numbers of patients using this as monotherapy 25…”
Section: Introductionmentioning
confidence: 99%